Animal models of polymicrobial pneumonia - Hraiech S; Papazian L; Rolain JM; Bregeon F (Dove Medical Press, 2015)
Sami Hraiech,1,2 Laurent Papazian,1,2 Jean-Marc Rolain,1 Fabienne Bregeon1,3IHU Méditerranée Infection, URMITE CNRS IRD INSERM UMR 7278, Marseille, France; 2Réanimation – Détresses respiratoires et Infections Sévères, APHM, CHU Nord, Marseille, France; 3Service d’Explorations Fonctionnelles Respiratoires, APHM, CHU Nord, Marseille, FranceAbstract: Pneumonia is one of the leading causes of severe and occasionally life-threatening infections. The physiopathology of pneumonia has been extensively studied, providing information for the development of new treatments for this condition. In addition to in vitro research, animal models have been largely used in the field of pneumonia. Several models have been described and have provided a better understanding of pneumonia under different settings and with various pathogens. However, the concept of one pathogen leading to one infection has been challenged, and recent flu epidemics suggest that some pathogens exhibit highly virulent potential. Although “two hits” animal models have been used to study infectious diseases, few of these models have been described in pneumonia. Therefore the aims of this review were to provide an overview of the available literature in this field, to describe well-studied and uncommon pathogen associations, and to summarize the major insights obtained from this information.Keywords: pneumonia, animal model, co-infections, polymicrobial, route of infection